2005
DOI: 10.1002/pros.20301
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatocyte growth factor activator inhibitor type I (HAI‐I) and type 2 (HAI‐2) in prostate cancer

Abstract: HAI-1 may be a potential tumor marker for prostate cancer. Further studies in large groups of patients are needed to define the clinical value of HAI-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…However, another study observed using immunohistochemistry indicated that HAI-1 expression levels were reduced in all grades of prostate cancer specimens (40). According to current research, HAI-1 may exhibit different functions in different types of cancer or even at different stages/sites in the same type of cancer (26,32,37,40,47). However, the differences in measuring HAI-1 expression levels, the lack of standardized methods (including antibody) among studies create difficulties in reaching a conclusion regarding HAI-1 expression in cancer and its association with clinicopathological parameters.…”
Section: Hai-1 Functional Domains and Proteases Inhibited By Hai-1mentioning
confidence: 59%
See 1 more Smart Citation
“…However, another study observed using immunohistochemistry indicated that HAI-1 expression levels were reduced in all grades of prostate cancer specimens (40). According to current research, HAI-1 may exhibit different functions in different types of cancer or even at different stages/sites in the same type of cancer (26,32,37,40,47). However, the differences in measuring HAI-1 expression levels, the lack of standardized methods (including antibody) among studies create difficulties in reaching a conclusion regarding HAI-1 expression in cancer and its association with clinicopathological parameters.…”
Section: Hai-1 Functional Domains and Proteases Inhibited By Hai-1mentioning
confidence: 59%
“…The mean serum levels of HAI-1 in 118 patients with prostate cancer were reported to be significantly higher than those in 27 patients with benign prostatic hyperplasia. Furthermore, increased HAI-1 levels in serum were associated with distant metastasis and the development of hormone-resistance in prostate cancer (47). However, another study observed using immunohistochemistry indicated that HAI-1 expression levels were reduced in all grades of prostate cancer specimens (40).…”
Section: Hai-1 Functional Domains and Proteases Inhibited By Hai-1mentioning
confidence: 96%
“…HAI-1 may have a role in the progression of many cancers (Parr and Jiang, 2006) and has been suggested as a serum marker for prostate cancer (Nagakawa et al , 2006). Expression of HAI-1 is inversely related to invasion and metastasis (Parr and Jiang, 2001), and low expression is considered to be an indicator of poor prognosis in some cancers (Nakamura et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of HGFA and reduction of HAIs have been reported in a variety of tumors, indicating that the disruption of the balance between HGF activation and inhibition may favor tumor formation [29,30,31]. In addition, clinical data show that HAIs are inversely correlated with patient prognosis in different types of cancers, which further strengthens the potential role of HAIs as novel prognostic markers [32,33,34,35,36,37]. Recent research evidence suggested the therapeutic potential of recombinant HAI proteins for the treatment of a variety of cancers, including prostate, breast, and ovarian cancer [35,38,39].…”
Section: Mechanism Of Action: Targeting the Hgf Ligand Vs Targetimentioning
confidence: 77%